Pengaruh Kecerdasan Emosional, Kecerdasan Spritual, Dan Lingkungan Kerja Terhadap Kinerja Pelayanan Keseharan (Studi Kasus Pada Tenaga Kesehatan RSI Unisma) - Takimpo, Arbin; Nurhidayah, Nurhidayah; Hardaningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aimed to analyze the influence of emotional intelligence, spiritual intelligence, and work environment on the performance of health services by healthcare workers at RSI Unisma. The research was conducted using a survey method with 54 respondents and employing a saturated sampling technique. The data analysis method used in this study was quantitative data analysis using multiple linear regression analysis. The data testing used was partial hypothesis testing (t-test). The results showed that emotional intelligence and work environment had a significant positive effect on the performance of health services, while spiritual intelligence did not have a significant effect. In conclusion, improving emotional intelligence and enhancing the work environment can improve the performance of health services by healthcare workers at RSI Unisma, but increasing spiritual intelligence does not have a significant impact on the performance of health services. Keywords : Emotional Intelligence, Spiritual Intelligence, Work Environment, and Health Service Performance